Chesapeake shores: Flowers on Main - Book 2 - Woods, Sherryl (Thorndike, Me. : Center Point Pub., 2009)
When she abandons Chicago and returns home to open a flower shop, writer Bree O'Brien finds her new life anything but peaceful when her estranged mother arrives and her former lover, Jake Collins, tries to run her out of town.
Keywords: Bed and breakfast accommodations -- Fiction; Large print books; Chesapeake Bay Region (Md. and Va.) -- Fiction; Love stories